Homoarginine in the cardiovascular system: pathophysiology and recent developments - Koch, Vitali; Grünewald, Leon David; Gruber-Rouh, Tatjana; Eichler, Katrin; Leistner, David; Mahmoudi, Scherwin; Booz, Christian; Bernatz, Simon; D'Angelo, Tommaso; Albrecht, Moritz H.; Alizadeh, Leona Soraja; Nour-Eldin, Nour-Eldin Abdelrehim; et al. (Fundamental & clinical pharmacology, 2023)
Upcoming experimental and epidemiological data have identified the endogenous non-proteinogenic amino acid L-homoarginine (L-hArg) not only as a novel biomarker for cardiovascular disease but also as being directly involved in the pathogenesis of cardiac dysfunction. The association of low L-hArg levels with adverse cardiovascular events and mortality has proposed the idea of nutritional supplementation to rescue pathways inversely associated with cardiovascular health. Subsequent clinical and experimental studies contributed significantly to our knowledge of potential effects on the cardiorenal axis, acting either as a biomarker or a cardiovascular active agent. In this review article, we provide a comprehensive summary of the L-hArg metabolism, pathophysiological aspects, and current developments in the field of experimental and clinical evidence in favor of protective cardiovascular effects. Establishing a reliable biomarker to identify patients at high risk to die of cardiovascular disease represents one of the main goals for tackling this disease and providing individual therapeutic guidance.
Erstmals veröffentlicht: 12. Dezember 2022
Gesehen am 01.07.2024